Advances in pediatric rheumatology. Issue 3 (June 2008) - Cimaz, Rolando; Prieur, Anne Marie
The future of pediatric rheumatology is certainly exciting. Advances in classification and our knowledge of etiopathogenesis have opened new fields in the diagnosis and management of common and uncommon conditions. Until the mid-1980s, therapy for children with chronic arthritis consisted primarily of a small repertoire of anti-inflammatory drugs and corticosteroids. With the more advanced understanding of the immune system and the advent of biologic agents in the 21st century, pediatric rheumatologists now have many more therapies to offer patients, with the expectation that their disease will be controlled. Disorders that are more specific to pediatric patients, such as systemic-onset juvenile idiopathic arthritis, Kawasaki disease and autoinflammatory diseases, will be discussed in more detail in this article.